2014
DOI: 10.1177/0269215514552035
|View full text |Cite
|
Sign up to set email alerts
|

Adult daughters providing post-stroke care to a parent: a qualitative study of the impact that role overload has on lifestyle, participation and family relationships

Abstract: Future support efforts should help daughters manage the caregiving role in light of other responsibilities. This can mitigate overload-related strain in valued relationships and decreased participation in valued activities, thereby contributing to better health and well-being for daughter caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 28 publications
3
45
0
3
Order By: Relevance
“…Like in previous studies, we found that the caregiving role leads to high levels of caregiver burden [36,37]. When reflecting on the time prior to the intervention, caregivers demonstrated strained relationships, decreased participation in valued activities and reduced physical activity [21]. Interestingly, caregivers who did not attend the MY-OT intervention saw little to no change in caregiver burden or positive aspects of caregiving.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Like in previous studies, we found that the caregiving role leads to high levels of caregiver burden [36,37]. When reflecting on the time prior to the intervention, caregivers demonstrated strained relationships, decreased participation in valued activities and reduced physical activity [21]. Interestingly, caregivers who did not attend the MY-OT intervention saw little to no change in caregiver burden or positive aspects of caregiving.…”
Section: Discussionsupporting
confidence: 80%
“…The ZBI is a 22-item questionnaire on which caregivers provide ratings (0-4, "never" to "almost always") about their perceptions of burden in their caregiving relationship. Total potential scores range from 0-88, with the following interpretations: little or no burden (0-20), mild to moderate burden (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), moderate to severe burden (41-60), severe burden (61-88). Items generally address the ideas of personal strain and role strain related to the impact of caregiving in the caregiver's daily life [30].…”
Section: Quantitative Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These adjustments impacted various aspects of life, from everyday routines, participation in occupations, and personal time. Examples of these adjustments included changes to the physical household environment, (Silva‐Smith, ), work schedules (Barbic, Mayo, White, & Bartlett, ; Silva‐Smith, ) living arrangements, (Bastawrous, Gignac, Kapral, & Cameron, 2; Coombs, ) and everyday routines (Silva‐Smith, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, caregivers reported changes to their abilities to participate in meaningful activities. Many described having to reduce involvement in leisure activities, such as exercising, (Bastawrous et al, ; Cao et al, ; Silva‐Smith, ), playing sports (Barbic et al, ; Bastawrous et al, ; Silva‐Smith, ) and travelling (Bäckström & Sundin, ; Barbic et al, ; Cao et al, ; Johnson, ; Silva‐Smith, ). Others discussed limited interactions with family and friends, (Buschenfeld et al, ; El Masry et al, ; Green & King, ; Saban & Hogan, ; Chow & Tiwari, ), often leading to feelings of social isolation (Buschenfeld et al, ; Kitzmüller, Häggström, Asplund, & Gilje, ; Chow & Tiwari, ).…”
Section: Resultsmentioning
confidence: 99%